Are Business Start-Ups Liquidity Constrained? Evidence from a Quasi-Experimental Allocation of Housing Wealth in East Germany - Tobias Fuchs; Georg Gebhardt (Center for Economic Studies and ifo Institute (CESifo), 2019)
Are entrepreneurs liquidity constraint? Using quasi-random housing wealth variation resulting from communist era decisions, we argue yes, as we find that wealthier East Germans are more likely to become self-employed after reunification. In the literature, no such strong relationship was found using regional house price changes the US and UK. In these economies, our results suggest, the effects of liquidity constraints are masked by anticipatory savings of the would be self-employed, which was impossible for the East Germans in our sample due to communism.
Keywords: J23; L26; G32; 330; self-employment; financial constraints; wealthy households; starting capital